EDUCATION ON FRONT-END DESIGN OF ELECTRONIC MEDICAL RECORD SYSTEMS USING ANGULAR TO IMPROVE CODING SKILLS - Arniti, Ni Ketut; Muliadi, Ade; Pratiwi, Nuning Indah (LPPM Univ. Ibn Khaldun Bogor, 2025)
The community service conducted at Universitas Pendidikan Nasional aims to provide education on designing the front-end of an Electronic Medical Record (EMR) system using Angular as an effort to improve students’ coding skills. The problems identified include participants’ limited understanding of Angular concepts and difficulties in designing a structured system interface. The activities were carried out through several stages, namely material preparation, interactive education, coding practice, and evaluation. The analysis shows an improvement in participants’ understanding of Angular project structure, skills in writing organized code, and the ability to build a simple EMR interface prototype. The conclusion of this activity is that practice-based education proves effective in enhancing students’ coding competence, while the recommendation is the need for continuous updates to the framework used so that the acquired skills remain relevant to technological developments.